The evolution of China's political economy - Marino, Rich (New York, NY : Routledge, 2023)
"For years, China's rapid economic transformation was hailed as a successful project that lifted hundreds of millions of people out of poverty. However, in recent times, the Chinese narrative has taken a more negative turn in the eyes of the West. Much of this has to do with the US perception about the role of the Chinese state in its economy and its military build-up, especially in the South China Sea. There's no question, China's complex economy can be difficult to understand. Information is often unclear and incomplete, and its data are not always reliable. However, this book presents the reader with a clear picture of China's economy and how it compares to other advanced economies, mainly the United States. The book unwraps the key features and structures of China's economy. Moreover, it examines and shows the similarities and differences in comparison with other like economies. In that effort, it underscores the differences by evaluating their benefits as well as their disadvantages, against the backdrop of China's incomplete transition to a market economy. This along with its governance structure becomes the crucial components shaping the way key stakeholders will act and react to opportunities and incentives as that economy evolves. The book supplements the definition of globalization for the academic, the student, the professional and anyone else interested in its positive and negative effects. It is also a good fit for anyone who wants to understand China's three elements of political economy: global trade, political power and its image on the global stage"--
Keywords: China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; China -- Politics and government -- 21st century; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / International / Economics; BUSINESS & ECONOMICS / Economics / Comparative